Academic Vocabulary and Reading Fluency: Unlikely Bedfellows in the Quest for Textual Meaning - David D. Paige; Grant S. Smith (MDPI AG, 2018)
Academic vocabulary is the specialized language used to communicate within academic settings. The Coxhead (2000) taxonomy is one such list that identifies 570 headwords representing academic vocabulary. Researchers have hypothesized that students possessing greater fluent reading skills are more likely to benefit from exposure to vocabulary due to greater amounts of time spent reading (Nagy and Stahl, 2007; Stanovich, 1986). In this study of 138 sixth- and seventh-grade students, we assess academic vocabulary, indicators of fluent reading, and silent reading comprehension to gain insight into relationships between the three. Our results found that reading rate mediates the relationship between academic vocabulary and reading comprehension, accounting for nearly one-third of the explained variance. Using simple slope analysis, we identified a threshold suggesting the point where reading rate exerts a neutral effect on reading comprehension beyond which vocabulary learning is no longer hindered.